2012
DOI: 10.1080/03004430.2011.649266
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic observation of social behaviours during preschool drop-off

Abstract: The present study utilised naturalistic observation to assess the impact of parental departure during daily drop-off at preschool on children's settling into daily preschool routines. Forty-six 3 -5-year-old children and their parents/caregivers were observed during morning drop-off at preschool. Longer latencies of parent/ caregiver leaving were associated with less child -peer engagement, solitary active play, and onlooking and were associated with more child -caregiver proximity-seeking, hugging and kissing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…More related to this study, Coplan et al (2015) studied schoolyard social participation and Vlachou et al (2013) observed rates of bullying among children. Much earlier Amato (1989) observed caretakers of children, while Grady et al (2012) used NO during preschool drop-off. Naturalistic observers documented, processed, and reported what they observed.…”
Section: Methodsmentioning
confidence: 99%
“…More related to this study, Coplan et al (2015) studied schoolyard social participation and Vlachou et al (2013) observed rates of bullying among children. Much earlier Amato (1989) observed caretakers of children, while Grady et al (2012) used NO during preschool drop-off. Naturalistic observers documented, processed, and reported what they observed.…”
Section: Methodsmentioning
confidence: 99%
“…Positive social behavior in preschoolers is characterized by three behavioral qualities (Grady et al, 2012). For starters, they employ a wide range of social abilities in a variety of situations.…”
Section: Social Interaction Interventions and School Readinessmentioning
confidence: 99%
“…297)." The social behavior of preschool children has been studied by researchers (Gesell, 1925) in preschool settings/environments (Lawrence, 2018), which are classrooms where children typically 3 to 5 years of age receive their formal education, for nearly a century (Berne & Van, 1930;Chandler et al, 1992a;Chittenden, 1942;Choi & Ohm, 2018 ;Grady et al, 2012;Jolstead et al, 2017;Lane et al, 2017;Marshall & McCandless, 1957;Parten, 1933 ;Parten & Newhall, 1943). Positive social behavior may be observed in preschool settings when the children function appropriately with others and their environment during designated class activities particularly when presented with social occasions including but not limited to free play.…”
Section: What Is Positive Social Behavior?mentioning
confidence: 99%